Training on the Use of Computer Applications in Making Learning Videos (Training for MTs Miftah Assa'adah Teachers) - Rufman Iman Akbar; Chaerul Anwar; Johannes Hamonangan Siregar (STMIK Pontianak, 2020)
This Community Service activity was carried out because they we the teacher's lack of ability in making their own learning videos. This ability is very much-needed in this pandemic, because students have to do distance learning. Universitas Pembangunan Jaya conducts training for teachers at MTs Miftah Assa'adah School located in South Tangerang area. In distance learning, the use of video media is needed by students. Teacher training is conducted using a combination of online and offline methods. The teachers were also given hand-on training to create, edit and upload the learning videos they made. Training using common applications and can be obtained easily. The applications used are also applications that do not require high computer resources, so they can be done with only standard devices. For example MS Power Point, Canva and Movie Maker, VLC and even Zoom. Of the 10 indicators used as a measure, 8 of them showed an increase of over 50%. The post-test results at the end of the training also showed an improvement in the general abilities of the training participants